Avaliação dos processos oxidativos UV/H2O2 e UV/PAA na degradação de matéria orgânica natural e 2-MIB/geosmina em água de abastecimento - Souza, Fernanda Scuissiatto Mares de (2012)
As a disinfectant and an oxidizing agent, chlorine is the most used chemical in various water may lead the formation of desinfection byproducts, furthermore, the inefficiency on micropollutants degradation. the main purpose of this work is to evaluate the efficiency of hydrogen peroxide (H2O2) and peracetic acid (PAA), in advanced oxidation process under UVC radiation, on degradation of natural organic matter and contaminats 2-MIB/geosmin in supplying water. The environmental matrix involved was water from Iratí River, located near Curitiba/PR. Waterpretreatment included coagulation, floculation and sedimentation operations at jar test equipement, with PAC as coagulant agent. Advanced oxidative treatments were executed at UV reactors, with low-pressure lamps, in batch and continuous mode. in UV?H@O@ treatment, maximum efficiency on UVA254 reduction (92%) and fluorescence (95%), was obtained in continuos flowing mode, after 15 minutes (reaction taime) and 15 mg.L-¹ of hydrogen peroxide, in the absence of 2-MIB and geosmin. The formation of total trihalomethanes was one of the lowest at 15.7 þg.L-¹. Degradation of pollutants 2-MIB and geosmin, after pretreatment and AOP UV/H2O2, ended in concentrations lower than 0.1 þg.L-1. According to these UV/H2O2 tests, certain reduction was obsorved at efficiency results of all response factors monitored, since the presence of methanol intrinsic to the contaminat standard solution applied. In UV/PAA, was noticed some contribution of NPDOC provided by the own oxidizing agent (PAA). However, UV/PAA treatment was efficient at 89% according to fluorescence intensity reduction, associated with the formation of total trihalomethanes at 21,5 þg.L-¹. Experimental analysis indicated positive and significant effect for the variable retention time in all tests. None of the tests resulted in carbon complete mineralization. Treatment with UV/H2O2 and Uv/PAA presented non-linear response profile, being necessary adjustments for quadratic fitting.